The Attitude of Post-Graduate Dental Students toward their Career Position and Future at Shahid Beheshti Dental School - reza amid; mahdi kadkhodazadeh; mahdie mirakhori; shirin shidfar; zahra nasabi (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: Taking back to many years ago, there are still some deficit in higher educational programs. One of the goals in every training system is to determine baseline and updated information regarding demands and attitudes of post-graduate students to predict the probable shortcomings. This study was performed to evaluate the attitude of post-graduate dental students to their position and future. Materials and Methods: This cross - sectional study was done on some postgraduate students of Shahid Beheshti dental school. Data was collected through a questionnaire whose reliability and validity had already been calculated. The questionnaire included different questions about their attitude toward the major courses, school, and the social status of dentists, etc. Mean scores of selected answers to specific 21 questions determined the final score via a range of 1-4 for each answers. The data was analyzed with SPSS version 16 and descriptive statistics were used for analysis. Results: The mean and SD score of the attitude of postgraduate students was 2.62 ± 0.3 (partly satisfied) that was more than the half of the total points score (2.5). Conclusion: Post-graduate students are seriously concerned about their job future. This requires special attention considering cultural and financial factors.